(untitled) (Communications in Computational Chemistry, 2025)
The inhibition of dewetting in polymer thin films (PTFs) is crucial for their practical applications. Through molecular dynamics simulations, we elucidate the mechanism of interface segregation of single-chain nanoparticles (SCNPs) in inhibiting PTF dewetting. Our study provides atomic-level insights into three key aspects: (1) how SCNP segregation affects the contact angle, (2) how it influences the orientation of matrix chains at the interface, and (3) how the interaction between solvent molecules and cross-linkers within SCNPs influences the dewetting behavior. By employing static droplet and dynamic pre-punched film models, we systematically investigate the effects of SCNP doping concentration and cross-linker-solvent interaction strength. Our results demonstrate that SCNP segregation significantly alters the orientation of linear polymer chains at the interface. In pure polymer films, chain ends preferentially accumulate at the interface due to entropic effects, leading to parallel chain conformations. However, SCNP segregation suppresses this effect, promoting more vertical chain orientations. Furthermore, we find that weaker cross-linker-solvent interactions promote SCNP segregation at the substrate interface, leading to more effective dewetting inhibition. These findings provide fundamental understanding and practical guidance for designing stable polymer thin films through nanoparticle doping.